Pengaruh Jarak Tanam dan Frekuensi Penyiangan Gulma pada Pertumbuhan dan Hasil Jagung Ketan (Zea mays var. Ceratina) - Apridhiani, Rafitah Muthiara; Sajar, Suryani; Harahap, Ariani Syahfitri (CV. Information Technology Training Center - Indonesia (ITTC), 2025)
This study aims to increase the growth and yield of glutinous corn which is efficient on the treatment of planting distance and frequency of weeding. This research was conducted at Gelugur Rimbun Research Field of Panca Budi Development University Medan. in Sampe cita Village, Kutalimbaru District, Deli Serdang Regency, North Sumatra Province with a factorial Randomized Group Design (RAK) consisting of 2 treatment factors. The first factor is the effect of planting distance consisting of 4 treatments namely J1 (50cm x 15cm), J2 (50cm x 30cm), J3 (50cm x 45cm), J4 (50cm x 60cm), the second factor is the effect of weed weeding frequency consisting of 4 treatments namely P0 (Weed free), P1 (7,14,21 days after planting), P2 (14,28,42 days after planting), P3 (21 and 42 days after planting), Each treatment was repeated 3 times. The results of this study showed that the effect of planting distance and weed weeding frequency had a significant effect on the number of fruiting parameters and had no significant effect on the parameters of plant height, stem diameter, number of leaves, leaf length, leaf width, flowering age, fruit length, fruit diameter, weight of weighted fruit, and weight of weightless fruit. Judging from the most dominant average value in this study on the effect of planting distance, there was a treatment of planting distance J3 (50 cm x 45 cm), and the effect of weed removal frequency did not produce the most dominant average value for all observation parameters.